2023
DOI: 10.1002/gps.5910
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional connectivity of the habenula in mild cognitive impairment patients with depression symptoms revealed by resting‐state functional magnetic resonance imaging

Abstract: Background: Recent research suggests that abnormalities in the habenula (HB), a core area of the brain that transmits reward information, may be a determinant of depression. However, it is not clear whether the functional connectivity (FC) pattern of the mild cognitive impairment (MCI) with and without depression symptoms is abnormal. Methods:In this study, we used resting-state functional magnetic resonance imaging (fMRI) to examine the FC pattern of the HB in MCI patients with depression symptoms (D-MCI). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 74 publications
(106 reference statements)
0
9
1
Order By: Relevance
“…As for Barreiros and colleagues (2022), they reported higher RSFC between the left habenula and the right precuneus in TRD patients compared to HCs and patients who were sensitive to treatment. Another study found that RSFC between the right habenula and the bilateral precuneus was higher in depressed patients with mild cognitive impairment (MCI) compared to patients who had MCI but were not depressed (Cao et al, 2023). In this study, however, no between-group difference was found for the left habenula.…”
Section: Dmn Regionscontrasting
confidence: 84%
See 4 more Smart Citations
“…As for Barreiros and colleagues (2022), they reported higher RSFC between the left habenula and the right precuneus in TRD patients compared to HCs and patients who were sensitive to treatment. Another study found that RSFC between the right habenula and the bilateral precuneus was higher in depressed patients with mild cognitive impairment (MCI) compared to patients who had MCI but were not depressed (Cao et al, 2023). In this study, however, no between-group difference was found for the left habenula.…”
Section: Dmn Regionscontrasting
confidence: 84%
“…Overall, four studies were similar enough to be compared (Cao et al, 2023;Ely et al, 2016;Qiao et al, 2020;Su et al, 2024). Among these studies, two found that depressed patients had lower RSFC between the habenula and the IFG (Cao et al, 2023;Su et al, 2024). One caveat is that in one study the results pertained to the left habenula, while they pertained to the right habenula in the other study.…”
Section: Other Regionsmentioning
confidence: 93%
See 3 more Smart Citations